Aflatoxin prevalence data collection: Sampling framework & methodology - Mahuku, George; Nzioki, Henry Sila; Waliyar, Farid; Diarra, Bamory; Kodio, Ondie (International Food Policy Research Institute, 2010)
Information is fragmented on the prevalence of aflatoxins, a variety of mycotoxin, in the maize value chain in Kenya and in the groundnut value chain in Mali. The purpose of this study is to generate a consistent database of aflatoxin prevalence along the maize and groundnut value chains through systematic sampling, and to identify critical points where intervention strategies are likely to have the greatest impact.